The trials and errors of developing an experimental model to study the impact of maternal gut microbiome disruption on perinatal asphyxia - Mara Ioana Ionescu; Ana Maria Catrina; Ioana Alexandra Dogaru; Didina Catalina Barbalata; Cristian Ciotei; Cerasela Haidoiu; Vladimir Suhaianu; Gratiela Gradisteanu Pircalabioru; Siobhain M. O’Mahony; Ana-Maria Zagrean (Reproduction and Fertility, 2024)
Maternal gut microbiome impairment has garnered attention for its potential role in influencing neurodevelopmental outcomes in offspring, especially in situations that increase brain vulnerability such as perinatal asphyxia (PA). Maternal microbiome and fetal brain interplay emerge as a critical link between maternal health and offspring neurodevelopment. This study aims to generate a model to assess the impact of maternal dysbiosis triggered by gestational antibiotic administration and PA on offspring neurodevelopment. Wistar rats were subjected to antibiotics in drinking water from the 11th gestational day until birth. On the 6th postnatal day, pups were subjected to PA/normoxia, resulting in four experimental groups: control-normoxia, antibiotics-normoxia, control-asphyxia, and antibiotics-asphyxia. Early-life behavioral tests were conducted between postnatal days 7 and 9. The initial antimicrobial cocktail (ampicillin, vancomycin, neomycin, clindamycin, amphotericin-B) led to an increased number of miscarriages, poor weight gain during pregnancy, reduced offspring weight, and changes in the maternal gut microbiome compared to control. Offspring presented impaired neurodevelopmental reflexes in both PA and antibiotic groups and increased hippocampal neuroinflammation. Due to these detrimental effects, a more pregnancy-safe antibiotic cocktail was used for a second experiment (ampicillin, vancomycin, neomycin, meropenem). This resulted in no miscarriages or pregnancy-weight loss but was still linked to gut microbiome disruption. PA impaired neurodevelopmental reflexes and increased neuroinflammation, effects amplified by antibiotic administration. These preliminary findings reveal the cumulative potential of maternal dysbiosis and PA on neurodevelopment impairment, emphasizing caution in gestational antimicrobial use. Further investigations should include offspring long-term follow-up and maternal behavior and integrate probiotics to counteract antibiotic effects.